Introducing the Neuroplastic Narrative: a non-pathologizing biological foundation for trauma-informed and adverse childhood experience aware approaches - Peckham, Haley (Frontiers in Psychiatry, 2023)
Most people accessing mental health services have adverse childhood experiences (ACEs) and/or histories of complex trauma. In recognition of this there are calls to move away from medical model approaches and move towards trauma-informed approaches which privilege the impact of life experience over underlying pathology in the etiology of emotional and psychological suffering. Trauma-informed approaches lack a biological narrative linking trauma and adversity to later suffering. In its absence this suffering is diagnosed and treated as a mental illness. This paper articulates the Neuroplastic Narrative, a neuroecological theory which fills this gap, conceptualizing emotional and psychological suffering as the cost of surviving and adapting to the impinging environments of trauma and adversity. The Neuroplastic Narrative privileges lived experience and recognizes that our experiences become embedded in our biology through evolved mechanisms that ultimately act to preserve survival in the service of reproduction. Neuroplasticity refers to the capacity of neural systems to adapt and change, and our many evolved neuroplastic mechanisms including epigenetics, neurogenesis, synaptic plasticity, and white matter plasticity allow us to learn from, and adapt to, past experiences to better anticipate and physiologically prepare for the future experiences that (nature assumes) are likely to occur, based on past experiences. However, neuroplastic mechanisms cannot discriminate between experiences; they function to embed experience regardless of the quality of that experience, generating vicious or virtuous cycles of psychobiological anticipation, to help us survive or thrive in futures that resemble our privileged or traumatic pasts. The etiology of the suffering arising from this process is not a pathology (a healthy brain is a brain that can adapt to experience) but is the evolutionary cost of surviving traumatizing environments. Misidentifying this suffering as a pathology and responding with diagnosis and medication is not trauma-informed, causes iatrogenic harm and perpetuates stigma. As an alternative, this paper introduces the Neuroplastic Narrative, situates it within an evolutionary framework complementing both Life History and Attachment Theory and demonstrates it provides a non-pathologizing, biological foundation for trauma-informed and Adverse Childhood Experience aware approaches.